Bone lesions of the tibia: Multimodal iconographic review and diagnostic algorithms, Part 2: Metaphyseal and epiphyseal lesions - Salmon, Vincent; Gondim Teixeira, Pedro Augusto; Blum, Alain (European journal of radiology Open, 2025)
This article focuses on the analysis of bone lesions of the tibia, addressing the main diagnostic challenges and imaging strategies used to characterize them. It examines the different etiologies of tibial lesions, emphasizing the importance of a systematic approach to distinguishing tumoral from non-tumoral lesions, as well as from bone dysplasia. The article underlines the essential role of imaging, particularly radiography, CT, and MRI, in accurate lesion characterization. It also highlights typical clinical and radiological features that help guide diagnosis and management. The main aim is to provide radiologists with clear guidelines for improving the identification of bony lesions of the tibia. Part 2 of this 2-part article proposes some illustrations of metaphyseal and epiphyseal lesions of the tibia. •Multimodal imaging enhances diagnosis of tibial metaphyseal and epiphyseal lesions.•Systematic imaging helps distinguish tumoral and non-tumoral bone lesions of the tibia.•Clinical and imaging features helps diagnostic approach of tibial bone lesions.